Zonally Asymmetric Influences of the Quasi-Biennial Oscillation on Stratospheric Ozone - Wang, Wuke; Hong, Jin; Shangguan, Ming; Wang, Hongyue; Jiang, Wei; Zhao, Shuyun (2022)
The Quasi-Biennial Oscillation (QBO), as the dominant mode in the equatorial stratosphere, modulates the dynamical circulation as well as the distribution of trace gases in the stratosphere. While the zonal mean changes in stratospheric ozone associated with QBO have been relatively well documented, the zonal (longitudinal) differences of the ozone signals related to QBO have been less studied. Here we demonstrate that the influences of QBO on stratospheric ozone are zonally asymmetric. Based on a composite analysis using satellite data, ERA5 reanalysis and model simulations, we found that the global distribution of stratospheric ozone varies significantly during different QBO phases. During QBO westerly (QBOW) phases, the total ozone column (TCO) and stratospheric ozone are anomalously high in the tropics, while in the mid-latitudes they are anomalously low over most of the areas, especially during the winter-spring of the respective hemisphere. This confirms the results from previous studies. In the polar region, the TCO and stratospheric ozone (50–10 hPa) anomalies are seasonal dependent and zonally asymmetric: during boreal winter (DJF), positive anomalies of TCO and stratospheric ozone are evident during QBOW over the regions from Greenland to Eurasia (60º W–120º E) in the Arctic while significant negative anomalies exist over other longitudes; in boreal autumn (SON), TCO and stratospheric ozone are anomalously high in the eastern hemisphere, but anomalously low in the western hemisphere over the Arctic; significant positive stratospheric ozone anomalies exist over the South America and Atlantic sector (60º W–60º E) of the Antarctic while negative anomalies of TCO and stratospheric ozone are seen in other longitudes during its spring (SON). The consistent features of TCO and stratospheric ozone anomalies indicate that the QBO in TCO is mainly determined by the stratospheric ozone variations. Analysis of meteorological conditions indicates that ozone anomalies associated with QBO are negatively correlated with temperature changes, suggesting that the QBO in stratospheric ozone is mainly caused by dynamical transport rather than temperature. QBO affects the geopotential height and polar vortex strength and subsequently the transport of ozone-rich air from lower latitudes to the polar region, which therefore influences the ozone concentrations over the polar regions. The geopotential height anomalies are zonally asymmetric with clear wave-1 features, which indicates that QBO influences the polar vortex and stratospheric ozone mainly by modifying the wave number 1 activities.